Minat Dan Kesiapan Diri Suksesor Dalam Suksesi Kepemimpinan Di Perusahaan Radio Swasta - Pramono, Cahyo; Nasution, Harmein; Trimurni Maas, Linda (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research was conducted in several family companies based in North Sumatra due to the presence of numerous private radio companies that can only manage their businesses for one to two generations. In this study, the variables of interest and successor readiness were used in the process of leadership succession in the researched private radio companies. The research was carried out descriptively using descriptive analysis, which was conducted through in-depth interviews. The research findings show that the interest of successors significantly influences the readiness of successors to take over leadership in private radio companies. Many private radio companies have not yet begun the succession process due to the interests of prospective successors. In order to improve their preparedness, successors often engage in capacity-building through various means, whether methodical or not. This shows the situation of many private radio companies that can only survive for one to two generations.